Industri Batik Garutan di Era Milenial (Studi Kasus Batik Garutan di Kabupaten Garut Jawa Barat) - Desi Qori'ah (Fakultas Ekonomi Universitas Garut, 2019)
The purpose of this study is to determine the development of the Garutan Batik Industry which is running in the Millennial era, how the production system is carried out, how is the distribution and the extent of demand from consumers. The research was conducted in Garut district. The research method applied is descriptive qualitative with data collection techniques using literature studies, observation and interviews with data sources. Garutan batik in the Millennial era is increasingly showing its existence both in local, national and even introduced to the international world. The results showed that the Garutan Batik Industry in Garut Regency showed an increase marked by the increase in Garutan Batik Industry players even though it was still in the home industry category, marked also by a marketing system that adopted the latest technology.